Karakteristik Fisikokimia, Sensori, dan Potensi Fungsional Flakes dari Tepung Komposit Mocaf dan Kelor dengan Penambahan Tepung Pisang Kepok - Simamora, Christin Katarina Vonbora; Puspawati, Gusti Ayu Kadek Diah; Wiadnyani, Anak Agung Istri Sri (Jurnal Teknologi dan Industri Pangan, 2026)
Flakes are ready-to-eat cereals generally made from wheat and commonly consumed as a crispy breakfast substitute. In this study, a blend of modified cassava flour (Mocaf) and moringa leaf powder is formulated to produce a gluten-free flake. Since the use of both ingredients may adversely affect the aroma and taste of the product, another ingredient, such as “kepok” banana flour, could be incorporated into the formulation. This study aimed to investigate the effects of “kepok” banana flour incorporation on the physicochemical and sensory characteristics of the flakes made from the composite of Mocaf and moringa leaf powder. A completely randomized design was applied with different levels of “kepok” banana flour (0, 15, 30, 45, and 60%), with each treatment replicated three times. The data were analyzed by using Analysis of Variance (ANOVA) and followed by Duncan’s Multiple Range Test to verify significant differences between means. The results demonstrated that the concentration of “kepok” banana flour significantly affected (p